2004
DOI: 10.1007/s00424-003-1219-4
|View full text |Cite
|
Sign up to set email alerts
|

GLUT11, but not GLUT8 or GLUT12, is expressed in human skeletal muscle in a fibre type-specific pattern

Abstract: Nine novel sugar transporter-like proteins have been discovered in the past 5 years. The mRNA for three of these, the glucose transporters (GLUT) GLUT8, GLUT11 and GLUT12, have been detected in human skeletal muscle. In the present study, we examined the pattern of expression and localization of the GLUT isoforms 8, 11 and 12 in human skeletal muscle using an immunohistochemical approach. Biopsies of human skeletal muscle from sedentary or trained healthy adults, from fetal muscle (24 weeks of gestation), from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 26 publications
3
32
1
1
Order By: Relevance
“…Endogenous GLUT11 protein was localized in heart and skeletal muscle with an antibody raised against the C-terminus of GLUT11 that does not distinguish between the different variants (117). Human GLUT11 is expressed exclusively in slow-twitch muscle fibers and is unaffected by physiological and pathophysiological conditions except in primary myopathy (117). Surprisingly, the human SLC2A11 gene has not orthologue in the rat and mouse genome (101).…”
Section: Glut11 (Slc2a11)mentioning
confidence: 95%
See 1 more Smart Citation
“…Endogenous GLUT11 protein was localized in heart and skeletal muscle with an antibody raised against the C-terminus of GLUT11 that does not distinguish between the different variants (117). Human GLUT11 is expressed exclusively in slow-twitch muscle fibers and is unaffected by physiological and pathophysiological conditions except in primary myopathy (117). Surprisingly, the human SLC2A11 gene has not orthologue in the rat and mouse genome (101).…”
Section: Glut11 (Slc2a11)mentioning
confidence: 95%
“…Mutational analysis of the DSV motif in GLUT11 that corresponds to the ''fructose'' transporter motif ''NAI'' showed that also in GLUT11 this particular region of helix 7 determines substrate selectivity of the transporter (13). Endogenous GLUT11 protein was localized in heart and skeletal muscle with an antibody raised against the C-terminus of GLUT11 that does not distinguish between the different variants (117). Human GLUT11 is expressed exclusively in slow-twitch muscle fibers and is unaffected by physiological and pathophysiological conditions except in primary myopathy (117).…”
Section: Glut11 (Slc2a11)mentioning
confidence: 98%
“…While the insulin-dependent transporter GLUT4 is continuously expressed from fetal life through mature adult muscle, GLUT1 and GLUT3 are found in fetal muscle but disappear around birth and are reexpressed only in regenerating fibers (256,257). Recently, expression of GLUT11 has been demonstrated in slow-twitch fibers, where it seems to be associated more with intracellular structures than to sarcolemma (258). This pattern of localization is strikingly different from that of GLUT4, which is associated almost exclusively with the plasma membrane in all fiber types (520).…”
Section: Trans-sarcolemmal Substrate Transportmentioning
confidence: 99%
“…GLUT5, also a member of the same transporter family, is a fructose transporter that seems to be insensitive to training (Hundal et al 1998). The less-frequently studied GLUT11 is unaffected by training (Gaster et al 2004). …”
Section: The Glucose Transporters Glut1 and Glut4mentioning
confidence: 98%